2015
DOI: 10.1007/s13196-015-0148-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microwave treatment on air permeability and preservative impregnation of Eucalyptus tereticornis wood

Abstract: Low permeability of many wood species causes problems during timber drying as well as impregnating with preservatives and resins. In the present study, microwave treatment of Eucalyptus tereticornis Sm. wood which is difficult to treat, was done at 2.45 GHz frequency at different levels of intensity and radiation time. The gas permeability of E. tereticornis wood was measured in an in-house built apparatus.Preservative uptake/retention was tested using Acid Copper Chrome preservative by dipping method. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Development of checks or cracks is desirable up to a certain extent as it can improve treatability of wood (Poonia et al 2015) as shown in Figure 2. …”
Section: Resultsmentioning
confidence: 99%
“…Development of checks or cracks is desirable up to a certain extent as it can improve treatability of wood (Poonia et al 2015) as shown in Figure 2. …”
Section: Resultsmentioning
confidence: 99%
“…Wood which is diffi cult to treat and dry is treated using a microwave at 2.4 GHz frequency, varying the radiation time and intensity. Further it was reported that treatment intensity and duration are increased, longitudinal wood permittivity increases signifi cantly [46]. Quercus infectoria (Oak) heartwood's tyloses structure was altered by microwave drying techniques, enhancing air permeability and diff usion coeffi cients.…”
Section: Impact Of Microwave Treatment On Permeability Of Woodmentioning
confidence: 99%
“…Notably, among the microwave-treated specimens, only Eucalyptus heartwood showed a reduction in compression strength parallel to the grain compared to the control group. Consequently, microwave treatment holds promise for expanding its applications within the wood industry [57]. Microwave treatment signifi cantly enhanced the permeability of Eucalyptus delegatensis.…”
Section: Impact Of Microwave Treatment On Permeability Of Woodmentioning
confidence: 99%
“…Rhatigan et al (2003) reported no differences in air permeability between lumber dried at conventional and high temperatures. Other studies revealed that heat treatment did not change the permeability of Populus robusta (Rousset et al, 2004) or subalpine fir (Abies lasiocarpa) (Poonia et al, 2015).…”
Section: Introduction Uvodmentioning
confidence: 96%